2012
DOI: 10.1517/17425255.2012.697152
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary evaluation of bardoxolone methyl for the treatment of diabetic nephropathy

Abstract: The development of an agent that leads to sustained improvement in renal function comes as a welcome relief to the millions of individuals with diabetes and CKD. However, much remains to be established regarding its actions in a complex and pleiotropic signalling cascade. Other triterpenoids with different PK/PD profiles are currently under development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Another Nrf2inducing compound is bardoxolone methyl, which has mainly been described as a potential treatment of chronic kidney disease. Although bardoxolone methyl has not so far been described in relation to GLO1 activation, its potential to induce Nrf2 may result in GLO1 induction [290][291][292][293].…”
Section: Glo1-inducing Compoundsmentioning
confidence: 99%
“…Another Nrf2inducing compound is bardoxolone methyl, which has mainly been described as a potential treatment of chronic kidney disease. Although bardoxolone methyl has not so far been described in relation to GLO1 activation, its potential to induce Nrf2 may result in GLO1 induction [290][291][292][293].…”
Section: Glo1-inducing Compoundsmentioning
confidence: 99%
“…38 Less well known Nrf2 activators include MG132, the specific, potent, reversible, and cell-permeable proteasome inhibitor, 39 and ebselen, the synthetic mimetic of the antioxidant enzyme, glutathione peroxidase-1 (GPx). 40 Our group previously has shown that ebselen reduced oxidative stress in animal models of T1D and attenuated diabetes-associated atherosclerosis and diabetic nephropathy.…”
Section: Nrf2 Activatorsmentioning
confidence: 99%
“…The C max was 25 ± 13 ng/mL and the C min was 8.8 ± 4.3 ng/mL. CDDO-Me also has low bioavailability, but this was improved by using an amorphous spray dried dispersion dosage form [124]. This highlights the potential pharmacokinetic advantages offered by novel delivery approaches.…”
Section: -Cyano-312-dioxo-oleana-19-dien-28-oic Acid-imidazolidementioning
confidence: 99%